2016
DOI: 10.1186/s12886-016-0266-5
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of vitrectomy with or without internal limiting membrane peeling for macular hole retinal detachment in the highly myopic eyes

Abstract: BackgroundTo evaluate the anatomical and visual outcomes by par plana vitrectomy with or without internal limiting membrane (ILM) peeling in highly myopic eyes with macular hole retinal detachment (MHRD).MethodsMEDLINE (Ovid, PubMed) and EMBASE were used for data collection up to September 30, 2015. The parameters of anatomical success, macular hole closure and improved best corrected visual acuity (BCVA) at or beyond 6 months after operation were assessed as the primary outcome measurement. The meta-analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 31 publications
0
25
0
3
Order By: Relevance
“…While no proved efficacy has been shown for this additional step in epiretinal membrane surgery [32], ILM peeling provided encouraging outcomes when associated with retinal detachment surgery [33]. When it comes to MHRD in highly myopic eyes, ILM peeling ensured a high rate of primary reattachment and macular hole closure, compared to non- ILM peeling [34]. However, the management of MHRD in highly myopic eyes is challenging and several surgical approaches have been proposed, including the inverted ILM flap technique [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…While no proved efficacy has been shown for this additional step in epiretinal membrane surgery [32], ILM peeling provided encouraging outcomes when associated with retinal detachment surgery [33]. When it comes to MHRD in highly myopic eyes, ILM peeling ensured a high rate of primary reattachment and macular hole closure, compared to non- ILM peeling [34]. However, the management of MHRD in highly myopic eyes is challenging and several surgical approaches have been proposed, including the inverted ILM flap technique [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…All MHRD cases reported in this series are primary cases, thus final reattachment and closure rates are not available which would explain the 25% reported closure rates. ILM peeling in addition to peeling of pre-retinal structures for MHRD are generally considered important to reduce traction and create Chorioretinal atrophy n = 52 a n (%) n = 27 n (%) n = The management of macular hole retinal detachment and macular retinoschisis in pathological myopia greater retinal redundancy for the closure of the macular hole [29][30][31]. However, according to the literature available, macular hole closure rates using OCT monitoring have generally been low and varied from 10 to100% and retinal reattachment rates have varied from 43 to 92% [29,[32][33][34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…There are also results suggesting that ILM peeling may reduce retinal sensitivity and significantly increase the incidence of microscotomas [ 48 ]. A meta-analysis of vitrectomy with or without internal limiting membrane peeling for macular hole coexisting with retinal detachment in the highly myopic eyes done by Gao et al revealed no definite benefit of postoperative visual improvement [ 49 ].…”
Section: Discussionmentioning
confidence: 99%